Adaptation of clinical guideline for nursing care of secondary brain injuries in adults - Marzieh Ziaeirad; Nasrollah Alimohammadi; Alireza Irajpour; Bahram Aminmansour (Tehran University of Medical Sciences, 2021)
Background & Aim: Traumatic brain injury management focuses on the prevention and treatment of secondary brain injuries. The aim of this study was to adapt a clinical guideline (CG) for nursing care of secondary brain injuries in adults. Methods & Materials: This study was carried out through a multi-stage evolutionary study at Isfahan University of Medical Sciences in 2017. Based on the opinions of experts using AGREE tool, the quality of 8 out of 13 CGs for the treatment and care of head injuries was assessed as optimal. These were used in drafting the adaptive CG. In addition, 12 CGs, 13 articles and 5 books were used to complete the recommendations of the mentioned guideline. The CG draft was evaluated using the Delphi method and the panel of experts. Finally, it was presented as an adaptive CG. Results: The adaptive CG for nursing care of secondary brain injuries was developed in 158 recommendations and five sections; nursing care to prevent and manage the increased intracranial pressure, nursing care to maintain and increase cerebral blood pressure, nursing care to prevent and control seizures, nursing care to prevent and control brain infections, and nursing care to prevent and control secondary extracranial injuries. Conclusion: The nursing staff of emergency and neurological wards and intensive care units can apply the recommendations of this clinical guideline to address some of the care needs of the injured patients and improve their health conditions.